Exploring Socio-economic Factors in Chilli Farming: A Multi Discriminant Analysis Approach in Andhra Pradesh - Kumari, Aruna A.; Kalpana, K. (International Journal of Economic Plants, 2025)
The present experiment was conducted during August, 2023 to March, 2024 in three districts of Andhra Pradesh (522 213), India i.e. NTR, Prakasam, and Kurnool, to examine the factors influencing farmers’ preferences for contract, non-contract, and Farmer Producer Organization (FPO) farming for chilly. The research included three villages from each district, resulting in a total of nine villages and a sample of 135 respondents representing three types of farmers. The findings revealed that FPO farmers had lower cultivation costs, were younger, owned more land (including rainfed land), had higher education levels, earned greater annual income, and cultivated larger land sizes with higher farm prices. In contrast, contract farmers were generally older and had more wetland, higher yields, and better market prices. However, contract farmers faced significant challenges, with increased risk (65.78%) associated with implementing good agricultural practices being a major concern. On the other hand, FPO farmers encountered limited access to markets (60.22%) as their primary constraint.